Prawo karne w państwie totalitarnym — casus Korei Północnej - Czechowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
It is hard to imagine that in the 21st century there is a state in which a joke, a yawn during a political speech or singing pop songs is punishable by death, and for accidentally breaking the bust of the chief, putting newspaper with his image on the floor or other manifestations of “disobedience” one can be sent to a concentration camp with one’s whole family — three generations back. Meanwhile, it is not just an Orwellian vision of the world, but the North Korean reality.This article aims to analyze the North Korean penal code and, consequently, to find the answer to the question of whether criminal law in the Democratic People’s Republic of Korea is an instrument of a totalitarian state policy and, if so, of what kind.
Keywords: prawo karne; totalitaryzm; Korea Północna; ideologia Dżucze; kara śmierci; obozy pracy; egzekucje przez pluton egzekucyjny